2014
DOI: 10.1063/1.4868702
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics based on fractional classical and quantum mechanics

Abstract: The purpose of this work is to study some problems in statistical mechanics based on the fractional classical and quantum mechanics. At first stage we have presented the thermodynamical properties of the classical ideal gas and the system of N classical oscillators. In both cases, the Hamiltonian contains fractional exponents of the phase space (position and momentum). At the second stage, in the context of the fractional quantum mechanics, we have calculated the thermodynamical properties for the black body r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…-обобщенная термическая длина волны [30]. Сравнение системы уравнений (29) с уравнением состояния свободного идеального бозе-газа [24] P…”
Section: конфайнмент идеальных бозе-газа и ферми-газаunclassified
See 1 more Smart Citation
“…-обобщенная термическая длина волны [30]. Сравнение системы уравнений (29) с уравнением состояния свободного идеального бозе-газа [24] P…”
Section: конфайнмент идеальных бозе-газа и ферми-газаunclassified
“…Результаты квантовой механики, полученные из понятия дробной производной, обсуждались некоторыми авторами [19], [21], [22]. В последние годы авторы работ [24], [25] обсуждали возможности введения этого понятия в квантовую статистическую физику и его физическую интерпретацию. Они также изучали некоторые проблемы теории квантовых статистических систем с энергетическим спектром дробно-степенного типа.…”
Section: Introductionunclassified
“…In this work, we investigate Bose-Einstein condensation through the Caputo-Fabrizio derivative [9] and compare our findings with those presented in [6]. Unlike Riesz and Caputo FD, the Caputo-Fabrizio derivative is improved, so that the kernel becomes non-singular.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, using the Green's function approach, they showed that these systems can emulate real systems with physical inter-particle interactions. In this context, [6] studied thermodynamic properties of 3D ideal Fermi and Bose gases, 3D independent harmonic oscillators, and black-body radiation. Interestingly, [5,6] found that the critical condensation temperatures of bosons with this spectrum are larger than in the standard ideal case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation